Semantics of the secondary forms based on the participles on -byt and -gan in the Yakut and Tuvan languages - Filippov, Gavril G.; Oorzhak, Bailak Ch. (The New Research of Tuva, 2020)
The article presents a comparative analysis of secondary forms that are based on semantically and functionally correlated participial forms in the Yakut and Tuvan languages. The forms ending in -byt and -gan occupy an important place in the verbal systems of the Yakut and Tuvan languages. In addition, these most striking typical Turkic participles, while retaining their proper participial functions, and acting in the sentence as a modifier, are used as a predicate in the main and dependent parts of the sentence. In their predicative function, they stand out among the main indicators of the past tense. These forms have the additional performance values and the temporal distance of the distant action. In combination with various affixes, service words and certain auxiliary verbs, the -byt and -gan forms create a number of synthetic and analytical secondary structures.The semantic structure of the system of secondary finite forms based on the -byt and -gan forms in the Yakut and Tuvan languages shows the direction of further development of their basic semantics in these languages. In the Yakut language, the 12 secondary -byt actualize the semantics of temporal distance, and the reliability of actions in the past. As a result, the meaning of the perfect is rethought to add the semantics of retelling and the admirative. In the Tuvan language, the meanings of mirativity, or indirect evidentiality, also developed into 4 secondary which make use of the -gan form.Secondary analytical structures combining the et-, -byt and -gan with auxiliary verbs of being regularly convey the meaning of the past relative and plusquamperfect, reflecting the general trend of building the system of relative tenses similar to the ones in other Turkic languages. Combinations of participles express grammaticalization of semantics of pretended action in -byt and -gan with auxiliary verbs buol- / bol-, which is typical for many Turkic languages.
Keywords: Yakut language; Tuvan language; participle; secondary forms; temporal distance; validity of action; perfectivity; mirativity; indirect evidentiality; relative time